Penerapan Metode Ummi Terhadap Peningkatan Kualitas Bacaan Al-Qu’ran di UPT SMAN 1 Pangkep - Maharani, Putri; Mustamin, Mustamin; Joharia, St; Ahmad, Ahmad; R, Muh Aidil Sudarmono (LP2M Universitas Islam Ahmad Dahlan, 2025)
This study evaluated the effectiveness of the Ummi Method in improving the quality of Al-Qur'an reading of class X Hemat students at UPT SMAN 1 Pangkep. Classroom Action Research (CAR) with two cycles, including planning, implementation, observation, and reflection, was used in this study. Data were collected through participant observation, interviews, tests (pre-test and post-test), and document analysis. The results showed a significant increase in students' Al-Qur'an reading ability after the implementation of the Ummi Method, including aspects of tajwid, makhraj letters, fluency, and self-confidence. Students' motivation and active participation in Islamic Religious Education learning also increased. Quantitative data analysis showed a significant increase in average scores from pre-cycle to cycle II; from 0% of students who achieved the Minimum Completion Criteria (KKM) of 75 in the pre-cycle to 90.32% in cycle II. These findings indicate the effectiveness of the Ummi Method in improving the quality of students' Al-Qur'an reading.